2017
DOI: 10.1038/oncsis.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

A distinct function of the retinoblastoma protein in the control of lipid composition identified by lipidomic profiling

Abstract: Here, by combining lipidomics with transcriptome analysis, we demonstrate that Rb depletion in mouse embryonic fibroblastss induces significant alterations in their lipid composition. We discovered that Rb depletion induced increase in lysophosphatidylserine, diacylglycerol (DAG), fatty acid (FA), acylcarnitine, phosphatidylcholine (PC), arachidonoyl ethanolamine, and decrease in phosphatidylglycerol, monoacylglycerol, without change in total lipid per protein levels. Analysis of the acyl chain composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
1
17
1
Order By: Relevance
“…While 20% of healthy secretion metabolites were supported via either experimental validation or literature curation, 22% of RB model metabolites were validated (Table S5). Furthermore, a recent study done on mouse embryonic fibroblast cells also identified that upon knockdown of RB gene resulted in significant changes of cellular lipid composition [64]. However, in the current study, majority of the model predictions with respect to secretion profile was for lipid class (i.e., 38%, Fig.…”
Section: Comparison Of Secretion Profilecontrasting
confidence: 47%
See 1 more Smart Citation
“…While 20% of healthy secretion metabolites were supported via either experimental validation or literature curation, 22% of RB model metabolites were validated (Table S5). Furthermore, a recent study done on mouse embryonic fibroblast cells also identified that upon knockdown of RB gene resulted in significant changes of cellular lipid composition [64]. However, in the current study, majority of the model predictions with respect to secretion profile was for lipid class (i.e., 38%, Fig.…”
Section: Comparison Of Secretion Profilecontrasting
confidence: 47%
“…3). Furthermore, a recent study done on mouse embryonic fibroblast cells also identified that upon knockdown of RB gene resulted in significant changes of cellular lipid composition [64]. Herein, we would like to emphasize on the need for targeted lipidomics experimentation for identification and validation of RB-specific metabolites that could aid in rapid medical diagnostics.…”
Section: Comparison Of Secretion Profilementioning
confidence: 97%
“…Increased ELOVL6 mRNA expression was found in triple-negative breast cancer tissue ( Yamashita et al, 2017 ). Additionally, ELOVL6 and lipid composition may be regulated by the RB-E2F transcription factor 1 pathway ( Muranaka et al, 2017 ). An ELOVL6 inhibitor, Compound A, inhibited tumor growth in an in vivo model of squamous cell carcinoma ( Marien et al, 2016 ), and therefore validation and pursuit of ELOVL6 inhibition in GBM is warranted.…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…Each sphingolipid was measured by LC-MS/MS with the Acquity UPLC system coupled with a 4000QTRAP triple quadrupole mass spectrometer (AB Sciex Pte. Ltd., Tokyo, Japan) equipped with an electrospray ionization source as described previously [48]. Briefly, the Acquity UPLC BEH-C18 reverse-phase column (1.7 µm particle size, 1.0 mm i.d.…”
Section: Measurement Of the Intracellular Sphingolipid Level By High-mentioning
confidence: 99%